Detection Oil Palm Tree Growth Variability using Field Spectroradiometer - Hashim, Mazlan; Ibrahim, Ab. Latif; Rasib, Abd. Wahid; Shah Ahmad, Rashdi; Nordin, Laili; Haron, Khalid (2001)
An analysis of average annual yield of fresh bunches of oil palm fruit in Malaysia showed clearly that there is spatial and temporal variability in yield. Various factors – such as environment, genetics, management, biotic stress – that occur across oil palm growing areas are known to be the main factors that cause yield variation. These variability factors are normally determined through an analysis of in situ measurement of related parameters, including corresponding environmental information. Systematic and accurate information regarding factors affecting oil palm tree growth and yield variability, such as water stress and the nutrition status of oil palm trees, is required. However, such as an analysis technique is very costly, timely and laborious in nature. Remote sensing techniques offer the most cost-effective method in obtaining such information. Crop growth performance can be identified and mapped using information obtained from remote sensing on the basis of spectral characteristics that have been widely accepted. This study demonstrates the potential of using remote sensing technique for detecting oil palm tree growth variability. Results of the study indicate that oil palm crop performance can be explained by analyzing the shape of spectral reflectance.